Oral health care in children with disabilities: a narrative review - Mustaffa, Musliana; Ismail, Ahmad Faisal; Mohd, Farah Natashah (IIUM Press, 2024)
Children with disabilities face discrepancies in receiving oral health services due to several barriers. This article aims to provide an overview on the oral health status of children with disabilities, impact on Quality of Life of children with disabilities and their family members, approaches in oral health education and/or services, roles of medical/oral health care providers, carers/parents, and special schools/centres, and future aspiration concerning these children. Articles were searched using online databases (Google Scholar, MEDLINE/PubMed) using various terms. Additional articles were searched manually from the reference list of the previously searched articles. Children with disabilities showed a higher prevalence of caries and periodontal disease and had irregular dental visits owing to the limitations encountered by the carers/parents. The psychological and physical health of carers/parents, and the well- being of children with disabilities are interrelated, suggesting the need for a comprehensive support system to address the specific needs of these groups. Oral hygiene care services for these children could be improved using oral health education tools, strengthening dental outreach programs, and/or adopting behaviour modification techniques. Oral health in children with disabilities is a global concern, therefore a holistic approach addressing this problem from the individual to international level, including interprofessional collaboration is imperative.